Innovaatiotoiminta: Näkemyksiä hyvinvointialaan ja työelämän kehittämiseen - Jari Hyvärinen (The Research Institute of the Finnish Economy (ETLA), 2011)
– This study examines structures and challenges in the Finnish well-being sector from the innovation activity perspective. Firstly, it compares the quality and productivity based on international statistics and research reports, and R&D&I activities in the well-being sector. It investigates also shortly co-operation and interplay between public and private actors, and the role of ICT for improving sector's productivity. In the end, the study explores well-being and quality of labour markets, and innovation activities in Finland.
Keywords: H51; H53; I11; J24; J81; 330; well-being; health; working life; productivity; innovation activity